Membangun Generasi Berintegrasi: Pendidikan Karakter dalam Kurikulum Nasional - Annisa ul Khaira; Devi Cynthia; Cut Kumala Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the important components of the national education system is character education, which helps produce a young generation with integrity, morals, and the ability to face the various problems of the modern world. Investigating implementation strategies in the classroom and examining how character education interacts with the national curriculum—specifically, the 2013 Curriculum and the Merdeka Curriculum—is the aim of this project. According to this study, which uses a qualitative descriptive approach through a literature study, character education is implemented comprehensively in various subjects as well as through intracurricular and extracurricular activities, with an emphasis on values ​​such as religiosity, nationalism, independence, mutual cooperation, and integrity. Teachers act as role models and facilitators, and schools and families work together to support children's character development. The study findings suggest that to create responsible, educated, and capable individuals who are ready to make significant contributions to society, effective character education emphasizes not only knowledge but also behavior and role models. Therefore, incorporating character education into the national curriculum is essential to raising a morally and ethically resilient generation today.